Keanekaragaman Terumbu Karang di Pantai Tiga Warna Kawasan Clungup Mangrove Conservation (CMC) Kabupaten Malang - Noercholis Mubarak (Journal of Biotropical Research and Nature Technology, 2024)
Coral reefs, as ecosystems that are crucial for the life of various marine biota, are formed by polyps and limestone skeletons produced by marine biota. This study aims to identify the types of coral reefs and assess the value of diversity at Tiga Warna Beach, Clungup Mangrove Conservation (CMC) area, Malang Regency. Carried out in July to August 2023, coral reef observations used the Underwater Photo Transect method, then the data were analysed with a coral reef identification book. Ten coral reef species were identified, including Acropora humilis, Acropora digitifera, Acropora palifera, Podabacia crustacea, Goniastrea retiformis, Echinopora lamellosa, Monstastrea annuligera, Goniastrea aspera, Pocillopora verrucosa, and Shymphyllia radians. The Shannon-Wiener Diversity Index (H') value obtained was 2.047, indicating the level of coral reef diversity is included in the medium category. This research provides important insights into biodiversity in the Tiga Warna Beach coral reef ecosystem, as well as contributing to conservation and environmental management efforts in the region.